Adaptive design theory and implementation using SAS and R - Chang, Mark (Chapman & Hall/CRC biostatistics series, 2008)
Examines drug development as an integrated process, illustrating practical applications with instructions. This book also includes SAS code and R source code. It also presents Bayesian approaches, which can be combined with adaptive design and trial simulation to form the ultimate statistical instrument for successful drug development programs.